Inherited recessive epidermolysis bullosa simplex in monochorionic twins - Hibbattino, Deon Raditya; Widianti, Nurani; Hikmah, Zahrah (Edelweiss Applied Science and Technology, 2024)
Epidermolysis bullosa (EB) is a rare disease characterized by skin disorders in the form of blister formation that is inherited in a recessive manner. The incidence of EB is estimated at approximately 1 per 50,000 births with a wide clinical spectrum. The main characteristics of EB are skin that is fragile and easily forms blisters, which often heal on their own but leave scar tissue. This study aims to describe the clinical presentation, diagnostic process, and conservative management of twins diagnosed with dystrophic epidermolysis bullosa. This study used a case report method from a journal that focused on two twins diagnosed with dystrophic epidermolysis bullosa. The primary focus of the study was on clinical presentation, diagnostic workup, and conservative treatment approaches. Blisters appear with varying degrees of severity and significantly affect the patient’s quality of life. A history of blistering or peeling lesions without an obvious cause should be explored further. The diagnosis is made based on clinical and histopathological findings. Epidermolysis bullosa has a serious impact on the patient’s quality of life, especially in severe cases such as twins with dystrophic EB. It is important to make an early diagnosis based on clinical presentation and histopathological examination to appropriately manage the condition and reduce further complications.